Russian Cosmism – the Theory of Media Epistemic Actions - K. A. Ocheretyany (Дискурс, 2019)
Introduction. The paper deals with the possibility of referring to a conceptual resource of Russian cosmism to clarify the position of a man in the modern media realism. Cosmist philosophers for the first time drew attention to the fact that the possible conquest of space will be primarily a rediscovery of man. Indeed, space devices mastered not so much space, as a man in his communicative nature, organizing new connections, new communities, new meanings.Methodology and sources. Methodologically, the research work is based on philosophical analysis of primary sources and research literature.Results and discussion. The paper shows that the cosmists managed not only to foresee the re-discovery of person, which will begin with an information explosion the release of meanings, images, events, signs, faces, etc. from the previous types of communication, they were the first to manage to point out the positive aspects of such emancipation and how to live after the information explosion. According to their intuitions: 1) a person will become open to all eras, all mythologies, all symbols, and therefore extremely complicated (today we see how the newest interfaces of technical devices force us to do more, maximally intensifying our psychophysiology – attention, reaction speed, etc. ); 2) in the conditions of increasing complexity, new types of organization will be required (today complex social and technical systems are intertwined, creating hybrids: virtual, augmented reality, real virtuality, etc.); 3) since traditional contexts are erased and paradoxical hybrid forms of experience are multiplied, actions should not just lead to some result, but first of all explain their goals and their meaning, that is, practical and pragmatic actions give way to epistemic actions (clarifying that actually done – hence the value of gamification, information, etc.). Thus, as a result of media research, through the prism of the philosophical search of cosmists, it is possible to see media not only as a message, but also as a community, which in conditions of the absence of a whole, understands this whole (space) as a task, as achieving a common mood through co-feeling, -co-readiness (organization), and an instrument for achieving attunement (the mood that precedes words, meanings, images, all their connections and remains after their emancipation), suggests epistemic actions – actions not only creating something, but also clarifying, what is being done.Conclusion. The theory of the common cause should be understood as the theory of epistemic actions in the media (or as the theory of media epistemic action), which becomes the basis for clarifying the mechanism of orientation, mutual understanding and mutual recognition in media reality, when a person cannot consume information, without participating in its production.